The Effect of the Jigsaw Learning Model on the Understanding of the Concept of Classifying Animals based on the Type of Food - Indiana Indah Laela Saroyah; Usep Soepudin (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study aims to determine whether the Jigsaw learning model influences the understanding of the concept of classifying animals based on the type of food and student activities when the Jigsaw learning model is applied. This research was conducted at SDN Sukamaju class V. The type of research used by researchers was quantitative with the Quasi Experimental Design method with the Nonequivalent Control Group Design research design, which involved 22 experimental class students and 22 control class students as samples. Collecting data in this study used a test in the form of Multiple Choice (PG) of 20 items. Based on the results of the study, it can be concluded that 1) The Jigsaw learning model influences the understanding of the concept of classifying animals based on the type of food in class V students. The experimental class has an average value of 84.32. This can be proven by the results of the percentage value of 70.57%. This proves that applying the Jigsaw learning model can increase student activity in the learning process.